FIGURATIVE LANGUAGE FOUND ON PAMUNGKAS ALBUM ENTITLED “BIRDY” TO TEACH POETRY - Diya Yanua Safitri; Fitri Yulianti; Sri Wahyuni (Melati Institute, 2023)
This research is conducted to analyzed types of figurative language of “Birdy” album by Pamungkas. The researcher describes the type of figurative language by Kenedy. The research used descriptive qualitative. The research findings of this final project can be seen in the following: First, there are 59 figurative language found in song lyric of Pamungkas album “Birdy”. Those 59 figurative languages divided into several types namely metaphor, irony, hyperbole, repetition, personification, and simile. The most dominant type of figurative language in this song lyric is hyperbole the researcher found 24 parts, followed with metaphor within 18 parts, repetition with 7 parts, simile and irony with 4 parts, and the last one is personification with 2 parts. Second, by using the song lyric, it can attract more students' interest because the song can be a modern and newest reference about figurative language in poetry teaching, understand material about figurative language, and also by using the lyrics of the song can add new vocabulary for students in a more fun way. And also for the teacher can find the modern and newest reference and the material to teach their student so this research contribution to poetry teaching.